2014
DOI: 10.1097/acm.0000000000000406
|View full text |Cite
|
Sign up to set email alerts
|

Educating Resident Physicians Using Virtual Case-Based Simulation Improves Diabetes Management

Abstract: Purpose To test a virtual case-based Simulated Diabetes Education (SimDE) intervention developed to teach primary care residents how to manage diabetes. Method Nineteen primary care residency programs, with 341 volunteer residents in all post-graduate years (PGY), were randomly assigned to a SimDE intervention group or control group (CG). The web-based interactive educational intervention used computerized virtual patients who responded to provider actions through programmed simulation models. Eighteen disti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 33 publications
2
37
0
1
Order By: Relevance
“…Some studies indicate that a significant number of graduates of primary care residency programs are inadequately trained in the outpatient diabetes care [17] and that formal diabetes management training can improve their ability to achieve goals of care [12,17]. Our results indicate that residents felt more confident in their ability to deliver appropriate prediabetes care after our one-hour training program and after working within our new program for 6 months.…”
Section: Discussionsupporting
confidence: 62%
“…Some studies indicate that a significant number of graduates of primary care residency programs are inadequately trained in the outpatient diabetes care [17] and that formal diabetes management training can improve their ability to achieve goals of care [12,17]. Our results indicate that residents felt more confident in their ability to deliver appropriate prediabetes care after our one-hour training program and after working within our new program for 6 months.…”
Section: Discussionsupporting
confidence: 62%
“…[12][13][14] Given that Project ECHO capitalizes on relationships and runs as a huband-spoke model, we believe that there may be value in expanding delivery by geographic region.…”
Section: Discussionmentioning
confidence: 99%
“…We noted the extent to which participants reported an increase in confidence as MS providers. Whereas some studies have demonstrated how case-based learning increases confidence, 20,21 we were also aware that casebased learning has the potential to decrease confidence by highlighting the extent to which an individual might lack important knowledge on the topic of interest. The neurologist), imaging/safety monitoring (two cases from less experienced neurologists and two from a less experienced physiatrist), symptom management (two cases from a less experienced physiatrist and one from an experienced physiatrist), and additional referrals (one case from a less experienced neurologist and one from an experienced neurologist).…”
Section: Discussionmentioning
confidence: 95%